Chlorophyllin sensitized carbon nitride scaffolds for photocatalytic application. (September 2020) - Bhoyar, Toshali; Vidyasagar, Devthade; Umare, Suresh S.
Graphical abstract: Highlights: Sensitizing chlorophyllin molecules bound to the CN surface via simple impregnation path. The incorporation of Chl into CN matrix significantly shifted the optical response towards a higher wavelength. Improved visible light absorption, and multiple photon absorption enhanced the degradation rate kinetics of Chl-CN hybrid. The degradation using Chl-CN afforded rapid photodegradation activity for RhB dye than the counterpart bulk CN. Abstract: Polymeric carbon nitride (CN) scaffolds are broadly investigated in photocatalytic energy production and environmental purification applications. However, the visible light absorption capacity of CN catalysts is limited to ∼460 nm. Herein, we attempt to extend the visible light absorption capacity of CN by surface sensitization approach and elevate its photoactivity. Modification of CN via immobilization with a photosensitizer such as chlorophyllin (Chl), is likely to extend, and enhance the photocatalytic reaction dynamics. Henceforth, a series of Chl-CN hybrids ( x C-CN) were prepared by the impregnation route, and thoroughly characterized to understand the physico-chemical properties. The effects of Chl-sensitization on the CN surface are extensively correlated to the observed photocatalytic dye degradation activity.